MUNICIPAL AUTONOMY VERSUS CONSTITUTIONAL SUPREMACY: THE UNCONSTITUTIONALITY OF THE JUAZEIRO/BA LAW ON BONUS LEAVE AND THE LIMITS IMPOSED BY THE JURISPRUDENCE OF THE STF AND STJ - Brito, Maria Victoria Souza Gonçalves; de Souza Junior , Mario Cleone; Delfim, Priscila Martins (Seven Editora, 2025)
This article analyzes the material unconstitutionality of Municipal Law No. 2,741/2017 of the Municipality of Juazeiro/BA, which establishes the compensation for the leave of absence for perfect attendance based on the initial salary of the public servant's career, to the detriment of the full remuneration in effect at the time of granting. Based on legal action, appeals, and the consolidated jurisprudence of the Supreme Federal Court (STF) and the Superior Court of Justice (STJ), the study demonstrates that this rule violates constitutional principles such as the irreducibility of salaries (art. 37, XV, CF/88), the prohibition of unjust enrichment, and acquired rights. Through bibliographic review and documentary research, it argues for the need to raise an incident of unconstitutionality in the Court of Justice of Bahia (TJ/BA), promoting the adoption of full remuneration as the basis for calculation to avoid social regression and harm to public servants. The results reinforce the supremacy of the Federal Constitution over municipal infra-constitutional norms, proposing judicial reform of harmful administrative acts.DOI: https://doi.org/10.56238/sevened2025.040-006